Professional Business Vocabulary in the Television Series Succession: A Character-Based Lexical Analysis - Pavlovska, Katrina (International Journal of Language and Literary Studies, 2026)
This study explores how professional business language is used in the television series Succession and how it helps create realism, shape characters, and construct power relationships. Drawing on research in English for Specific Purposes, Business English, and media discourse, it examines how scripted dialogue mirrors real corporate communication while also advancing the story and developing character identities. The analysis is based on a 19,485-word corpus compiled from the first three episodes of Season One, from which 505 business-related lexical items were manually identified and categorised using an adapted semantic framework. Both quantitative and qualitative methods were used to track patterns across episodes and to examine how particular terms operate within interactions. The findings show that the focus of business language shifts as the narrative develops, moving from leadership and succession issues toward finance and operations. Characters also display distinct ways of speaking: Kendall uses the widest range of business terms, Gerri relies heavily on legal language, Roman adopts strategic vocabulary, Shiv favours HR-related discourse, and Logan speaks less but with clear authority. Overall, the study shows that business language in Succession actively builds power, identity, and hierarchy rather than simply reflecting corporate settings.